Den emotive metro. Louis-Ferdinand Céline og vidnesbyrdlitteraturen - Hansen, Troels Hughes (Passage - Tidsskrift for litteratur og kritik, 2013)
Troels Hughes Hansen: “The Emotive Metro. Louis-Ferdinand Céline and Witness Literature” The article proposes a new angle on the last novels of the French writer Louis-Ferdinand Céline (1894-1961). It is suggested that certain formal traits of the so-called German Trilogy can be regarded as more or less analogous to themes and problems normally associated with witness literature. This interpretation adds an ethical dimension to Céline’s oeuvre insofar as his chronicle incorporates the voices of an exiled community and thereby in a certain manner speaks for a group more or less damned by official history. Knowing, however, that his testimony will not be easily accepted by the public because of the author’s collaboration, Céline develops a literary style designed to reach a hostile reader on an emotional rather than a rational level.